Influence of Food Pigments and Thermal Aging on the Color Stability of Denture Base Resins - Beatriz Costa; Cristina Bettencourt Neves; João Carlos Roque; Vitor Anes; Virgínia Santos (Applied Sciences)
Color stability of acrylic resins is essential for preserving the aesthetic appearance of denture bases over time. This study explores how food pigments and thermal changes affect the color stability of commonly used denture base resins. Four acrylic resins were tested: three heat-cured acrylic resins with different characteristics (Zhermack® Villacryl H Plus V2, H Plus V4, and H Rapid FN V4) and one self-cured acrylic resin (Zhermack® Villacryl S V4). To simulate the oral environment, the resins underwent 1000 thermal cycles between 5 °C and 55 °C, followed by a 7-day immersion period in beverages such as coffee, red wine, a caramel-colored soft drink (cola), and distilled water (control), forming sixteen group of specimens (n = 5). Color changes (∆E) were measured using the VITA Easyshade V® spectrophotometer, following the CIEDE2000 standard. The findings revealed that thermal aging caused noticeable color changes in all resins (p < 0.001). Red wine led to the most intense discoloration, followed by coffee. The caramel-colored soft drink caused moderate staining, while distilled water had a negligible effect. The type of polymerization did not affect the degree of discoloration, as no significant differences were found between the resins after exposure to beverages (p > 0.05). Overall, this study highlights how both internal and external factors impact the appearance of acrylic resins. Thermal aging can accelerate polymer degradation, while pigments in beverages cause visible staining. Among the tested beverages, red wine proved to be the most aggressive due to its high pigment concentration and low pH. These findings emphasize the need for improved material formulations to enhance the longevity and aesthetic performance of dentures.